The Influence of Price, Brand, and Product Quality on Purchase Decisions in the Marketplace JD.ID - Sherly Fransisca; Pujiarti Pujiarti (Komunitas Dosen Indonesia, 2022)
The purpose of this thesis is to see how far the price, brand, and product quality on purchasing decisions have an influence on the JD.ID marketplace. The sample selection was based on the simple random sampling method. From multiple linear regression of the price variable on purchasing decisions the value is 3.197 > t table 1.985 with a level of sig 0.002 <0.05, the results of the t-count value of the brand variable are t count 1.985 = t table 1.985 and sig 0.050 = 0.05, then the quality variable product on purchasing decisions t count 2.306 > t table 1.985 and sig 0.023 <0.05, which means this test statistically proves that the independent variable has a positive effect on purchasing decisions. From the coefficient table, the linear equation Y= 8.057 + 0.350 X1 + 0.241 X2 + 0.239X3+ e means that for every 1 point increase or decrease in price, brand, and quality, the purchasing decision will increase or decrease by the number of independent variables. R Square of 0.570 or 57%, meaning that the magnitude of the influence of price, brand, and product quality on purchasing decisions is 57% and the rest is influenced by other factors. Based on the ANOVA table, the F value is 42,339 with a sig level of 0.000 <0.05. The results of the F test show that all independent variables have a simultaneous influence on purchasing decisions (Y).